(untitled) (Research, Society and Development, 2021)
Introduction: Suicidal ideation is a key element of a process called suicidal behavior, which includes: planning, attempting, and the actual suicide. It is a path that goes from motivation and suicidal ideation to planning the method and self-aggression. Brazil ranks 11th in the world for suicides. Objective: to identify epidemiological profile of suicides reported in the state of Pará in the year 2019. Materials and Methods: Descriptive epidemiological study, based on data of Suicide occurred in the State of Pará in the year 2019, registered in the Mortality Information System and made available by the Department of Informatics of the Unified Health System Results: In the year 2019, 348 suicides were reported in the State of Pará, with the municipalities of Belém (55 cases), Santarém (18 cases) and Itaituba (18 cases), the cities with the highest occurrence; as for the gender variable, there was a prevalence of male gender, with 272 (78.16%); regarding the age range, 88 cases (25.3%) were between 20 and 29 years old, followed by the age range between 30 and 39 years old presenting 73 cases (21%). Conclusion: It was found that although the importance of nurses in this theme is well evidenced, as well as the high rates of suicides in Brazil, especially in the state of Pará, the number of studies that describe the relationship between nursing professionals and suicidal behavior is still low.